„VI ISLAMISTER.. Distinktion og drama i islamisk aktivisme - Christiansen, Connie Carøe (Tidsskriftet Antropologi, 1998)
Connie Carøe Christiansen: “We, Islamists”. Distinetion and Drama in Islamic Activism In the town of Fes the Islamic activists have now accepted Islamist as a term of selfdesignation. In the continuous drama of a rivalry between comrades and Islamists at the university campus, the Islamists are recreating themselves as Islamists. This struggle, as well as other activities of the Islamists, is reinforcing an objectifying approach to the world. The social space of the university is a polarized space where both political groups are trying to obtain visibility by various activities on the campus, which in a sense can be regarded as a stage. Their offer of a political standpoint, however, is often rejected and the vast majority of the Moroccan youth present themselves as uninterested in politics. They are in reality exeluded from formal political participation. The ability to objectify may act as support for the ascendent middle class in Morocco where politics has been tumed into an activity for elite families which are allied with the powerful king, Hassan II. At the university, however, political organizing is something that is quite easily accomplished, but at the same time it is monitored and controlled by the police. The political activities of the university students, therefore, have little real effeet, which only adds to the impression of them as exaggerated, as if having a melodramatic character. The Islamist, female students are not involved in the physical confrontations between comrades and brothers. Rather, necessitated by stereotype ideas on the Muslim woman as dumb and duil, they are engaged in a struggle of distinction. In this struggle they are implicitly distancing themselves from their “ordinary Muslim” sisters, the uneducated Muslim woman and the female students who let the religion play a minor part in their lives. This also involves objectifying processes. The Islamist women place impetus on the hijab but have also realized that this device does not suffice as a signal of commitment to the Islamist cause, because anybody can wear a hijab, calling for evemew devices of distinction. At doser look, the Islamists may have more in common with their secularist rivals than might be expected if one judges from the dramatic rivalry at the university. The women at least seem to be more concemed with distancing themselves from the ordinary Muslim woman, in order to make it possible to be recognized as being, at one and the same time, a woman, a Muslim, and an intellectual.